2004
DOI: 10.1192/bjp.184.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Mental health survey of the adult population in Iran

Abstract: Prevalence rates are comparable with international studies. There is a wide regional difference in the country, and women are at greater risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
270
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(317 citation statements)
references
References 10 publications
34
270
13
Order By: Relevance
“…Another study estimated the prevalence of anxiety and depression in a local Iranian population were 20.8 and 21% (22) . Frequency of mood and anxiety disorders in IBS patients evaluated in several studies and Frequency of 5%-15% for depression and 16%-19% for Anxiety have been reported (12,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Another study estimated the prevalence of anxiety and depression in a local Iranian population were 20.8 and 21% (22) . Frequency of mood and anxiety disorders in IBS patients evaluated in several studies and Frequency of 5%-15% for depression and 16%-19% for Anxiety have been reported (12,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a high prevalence of mental disorders in Iran with higher percentage in women (25.9%) than men (15.9%) (Noorbala et al 2004). Despite the potentially serious consequences of postpartum depression, it is unfortunate that the high percentages of postpartum depressive cases are not detected due to misdiagnosis or lack of self-awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, concomitant addiction to both narcotics and alcohol did not increase the chance of criminal activity. On the other hand, some studies (14,15) reported that the probability of criminal activity is higher in the case of multiple drug use. Chaiken et al (24) also reported that the rate of criminal activity in multiple drug users in the USA was 10 -20 times higher than the rest of drug abusers (15).…”
Section: Discussionmentioning
confidence: 99%
“…Likert scoring method of GHQ showed a cutoff point of 23 (scores higher than 23 indicate a mental disorder). The sensitivity, specificity, and the overall misclassification rates are of 70.5%, 92.3%, and 12.3%, respectively (15,18).…”
Section: Methodsmentioning
confidence: 99%